عہدنبویﷺمیں تعلیمی اداروں کا قیام سیرت کی روشنی میں: The establishment of educational institutions in the era of the Prophet (peace be upon him) in the light of biography (Khairulummah, 2023)
The above-mentioned statements of Islamic historians and biographers make this fact very clear that: The Messenger of Allah, may Allah bless him and grant him peace, used to invite the Muslims who came here to Islam, and those who came here used to leave blessed. And he struggled for the exaltation of Islam. Multa used to teach him the call and commandments of the religion of Islam. Yes, madrasahs were not organized like today, but whoever wanted to learn education would come and attend the service of the Holy Prophet (PBUH) and learn the commandments.Dar al-Raqam was a center of comfort for the Muslims, especially the poor, oppressed and oppressed and slaves used to come and take shelter here.Here, the duties of remembrance of Allah and sermons were also performed continuously. The Messenger of Allah (peace and blessings of Allah be upon him) used to pray together with his followers. It is also clear from Hazrat Khabab's statement that the benefactor of humanity used to pray to Allah Almighty here even at night for God's guidance.In this house, the performance of the preachers of Islam was evaluated, future plans of preaching were made and the hard work of training the preachers themselves was also done. Among the trained teachers of Dar al-Raqam, Hazrat Abu Bakr, Khabab bin Alarat, Abdullah bin Masoud and Musab bin Umayr are particularly noteworthy.Dar al-Raqam was the "Dar al-Islam" as well as the "Dar al-Shura" for the Muslims, in which future preaching plans were made through mutual consultation. The decision to migrate to Abyssinia was also decided here through mutual consultation, and this place had the same place in the history of Islam as Darulandah had with the Quraish.The refuge of the Messenger of Allah (peace and blessings of Allah be upon him) in Dar al-Raqam was a history-making stage and it was also an event like Halaf al-Fadhul, Harb al-Fajr and Aam al-Fail. The Meccans also determine the events that happened in the era of Prophethood in terms of before and after the entry of the Messenger of Allah (peace and blessings of Allah be upon him) into Dar al-Raqam.Hazrat Arqam was one of those people who were exalted by the wealth of Islam and he dedicated his house for educational, training and da'wah activities in the beginning. Jumki was considered the most important center for spreading Islam during his period.In the light of different statements of historians, it can be said that the period of stay of the Messenger of Allah (peace and blessings of Allah be upon him) in Dar al-Raqam was more than one year.The infidels were fully aware of the refuge of the Meccan Muslims in Dar al-Raqqam; however, they were not aware of the inner activities and plans of Dar al-Raqqam.There is also a clear indication of the presence of the Companions in Sha'ab Abi Talib. As much as the revelation was revealed during this period of siege, surely the Messenger of Allah (peace and blessings of Allah be upon him) would have taught it to the Companions in Shub Abi Talib and here the Companions would also discuss religious matters. In this sense, the community of Abi Talib can also be described as a da'wah center of the Makkah era of Prophethood, where the Messenger of Allah (peace and blessings of Allah be upon him) and his companions were engaged in teaching and preaching for three years.The last thing is that we should learn from the teachings of the Holy Prophet in the present age. In the above lines, the propagation and propagation of Islam in the Makkah and Madani period has been presented with great wisdom and expediency. This is a model for all humanity.